Analisis Kemampuan Matematika Siswa MTs Nurul Huda Mangaran dalam Menyelesaikan Soal PISA - Anggraini, Azza Liarista; Musyarofah, Alivinda Aulia Safira (Indonesian Journal Publisher, 2023)
Mathematics plays a very important role in various aspects of human life. Furthermore, learning mathematics can enhance logical, critical, systematic thinking, and problem-solving abilities, which are highly beneficial in daily life. This research aims to analyze the reasoning and problem-solving abilities of students at Mts Nurul Huda Mangaran in Situbondo through the completion of PISA 2012 questions, which the students had not encountered previously. The research approach used is qualitative, allowing the researcher to directly communicate with the respondents to assess the mathematical abilities of the students. Based on the data analysis conducted on 21 respondents, it is evident that the majority of students cannot answer these questions correctly. The challenge they face is difficulty in interpreting the issues presented in the questions. In questions related to inductive reasoning, students are capable of providing answers. However, for deductive reasoning questions, students still struggle to solve the problems presented in the questions.